2009
DOI: 10.1002/crat.200800239
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of glycine doped bis thiourea cadmium chloride single crystal

Abstract: Single crystal of 2 mol% glycine doped Bis Thiourea Cadmium Chloride, a semi organic nonlinear optical material has been grown by slow evaporation technique. Good quality single crystal with dimension 14 × 12 × 5 mm3 was harvested after 35 days. The influence of amino acid glycine was studied for 1, 2 and 3 mol% glycine doped Bis Thiourea Cadmium Chloride by Kurtz and Perry powder second harmonic generation test and compared with pure Bis Thiourea Cadmium Chloride which confirms the enhancement of second harmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The amino acids are organic materials for NLO application as they have donor carboxylic (COOH) group and the proton acceptor (NH 2 ) amino group, known as zwitter-ions. Therefore, amino acids can be used as dopants and it was observed that there is enhancement in the material properties such as NLO and ferroelectric properties [6]. L-lysine posses a side chain with hydrogen atom which offers to charge transfer to form semiorganic crystals for nonlinear optical applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…The amino acids are organic materials for NLO application as they have donor carboxylic (COOH) group and the proton acceptor (NH 2 ) amino group, known as zwitter-ions. Therefore, amino acids can be used as dopants and it was observed that there is enhancement in the material properties such as NLO and ferroelectric properties [6]. L-lysine posses a side chain with hydrogen atom which offers to charge transfer to form semiorganic crystals for nonlinear optical applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, all of the polymers exhibited similar spectral profiles. The intense adsorption band at 1729 cm -1 was assigned to carbonyl groups from EGDMA [38], whereas the adsorption band of C=S was observed at 1393 cm -1 [39,40]. The absorption band at 1465 cm -1 can be assigned to N-C-N stretching vibration [39].…”
Section: Characterization Of CD (Ii) Ion-imprinted Polymermentioning
confidence: 90%
“…Along the phase-matching angle, its SHG efficiency is almost similar to that of urea. It is a promising NLO crystal for different applications in the area of laser and optoelectronic [8,[19][20][21].…”
Section: Island Typementioning
confidence: 99%